(Acetylacetone isonicotinoylhydrazonato-kappa 3 O,N',O')dioxidovanadate(V) monohydrate - Wong, H.W.; Lo, K.M.; Ng, S.W. (International Union of Crystallography, 2010)
The hydrazone anion in the title compound, [V(C(11)H(12)N(3)O(2))O(2)]center dot H(2)O, is zwitterionic as its pyridyl N atom is protonated; the O, N and O' atoms span the axial-equatorial-axial positions of the trigonal-bipyramidal coordination polyhedron of the metal atom. All non-H atoms lie on a crystallographic mirror plane apart from the oxide ligands, which are related by mirror symmetry. The pyridinium N atom acts as a hydrogen-bond donor to the solvent water molecule, which is in turn a hydrogen-bond donor to the both oxide ligands. These hydrogen-bonding interactions give rise to a three-dimensional network motif.